DEVELOPMENT OF HOTS ORIENTED COGNITIVE PROBLEMS IN THERMODYNAMICS FOR SENIOR HIGH SCHOOLS - Agustihana, Seftyan; Suparno, Suparno (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
One of cognitive abilities of students that should be trained and developed in the 21st century learning is high-level thinking skills. As higher order thinking skills are emerging trend in education, assessment instruments based on high order thinking skills (HOTS) principles are required. This study aims to develop a high-level thinking ability instrument for Physics subject of senior high schools which is intended to measure HOTS of senior high school students for Thermodynamic Materials in City of Nganjuk in East Java. The study was conducted in three stages, including initial development, trials, and measurement. The initial development stage included compilation, review, and validation, including content validation by experts. There are two sets questions A and B, consisting 20 questions respectively, with anchor items as much as 5 items. The measurement results show that HOTS-oriented test kits of Thermodynamics have obtained empirical evidence are suitable with partial credit model. The difficulty level of the test battery is in the range of -2.0 to +2.0, with the most difficult aspects in the sequence are analyzing, evaluating, and creating. The reliability of HOTS-oriented tests has met the high categorical requirements, and based on the total information function of the tests, it is appropriately used to measure the HOTS of learners with capability -2.3 to +1.6. Based on students? responses, the analysis ability is the highest skills followed by the ability to evaluate and create. HOTS-oriented tests developed can be used as the reference for the teachers to accommodate student?s higher order thinking skills.